The Implementation Of The Distance Learning Period The Pandemic Of Covid-19 In MAN 1 Labuhanbatu Utara - nurliasiregar; Irham Huspa K. Siregar; Kurnia Putra (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
This research describes about the implementation of the learning period of covid-19 in MAN 1 Labuhanbatu Utara. The purpose of this thesis, namely: (1) Knowing the implementation of distance learning the covid-19 case studies: in MAN 1 Labuhanbatu Utara; and (2) Determine the factors inhibiting the learning of the covid-19 in MAN 1 Labuhanbatu Utara. Research using qualitative methods. Source of research data include primary sources (the head of the school, the homeroom MAN 1 Labuhanbatu Utara, guardians/parents) and secondary sources in the form of documentation and so on. Data collection techniques with interviews and documentation. Step analyze the data by reducing, presenting, and then conclude the data. The processing of the validity of data using triangulation of sources and methods. The results showed the Implementation of distance learning in MAN 1 Labuhanbatu Utara, namely socialization kaldik curriculum emergency covid-19, held a workshop and socialization to the guardians of the students. Teachers prepare RPPM and RPPH emergency, make the introduction video and teachers of the school environment, whatsapp group for sharing tasks, making the video tutorial and learning activities of learners, voice note to the introduction of the religious, and the sheet checklist for habituation day-to-day in the house. The factors that mengahambat the implementation of the learning of the emergency period of covid-19 in MAN 1 Labuhanbatu Utara, namely from the internal factors of the teacher, external factors, a tool supporting the android mobile phone, and internet quota